Le plan du métro comme métaphore spatiale et cognitive dans la visualisation - Audilio Gonzales-Aguilar; Coleta Vaisman (Netcom)
The starting point of our article is the subway map as a mediating interface between the territory and the user of the transmission network. This map is a topographic representation, with the Beck diagram, has evolved into a topological model. Our methodological approach has four points: the metro map seen as a dialogue between topography and topology; the map used as a viewing system; interactive map as spatial metaphor and the card as knowledge representation model. On this basis, we want to show this card, excluding geographical context, is a form of visual metaphor. Our work shows the importance of information visualization and its spatial representations with Metro metaphor. Our goal will be to establish bridges between the conceptual spatial metaphor and cognitive metaphor interactive maps to move towards the use of the subway map as a visual representation of universal knowledge.